Effect of Surgical Mask use on Peak Physical Performance During Exercise Treadmill Testing-A Real World, Crossover Study - Dalakoti, Mayank; Long, Cheryl; Bains, Arshia; Djohan, Andie; Ahmad, Isabel; Chan, Siew Pang; Kua, Jieli; Chan, Po Fun; Yeo, Tee Joo (Frontiers in Physiology, 2022)
Background Mask wearing is an essential strategy to combat the spread of SARS-CoV-2. Some individuals may wear masks during physical activity to reduce disease transmission. This study aimed to investigate the real-world effect of wearing a surgical face mask on physiological parameters at peak exercise in healthy individuals. Methods In this crossover design study, participants underwent maximal treadmill electrocardiogram exercise tests using the Bruce protocol with and without surgical mask. Heart rate, oxygen saturation, blood pressure, rate pressure product, metabolic equivalents (METS) and total exercise time were measured. Subjective rate of perceived exertion was also assessed. Results 50 adults (mean age = 31.7 ± 6.5 years; 27 males) completed both treadmill tests. Mask wearing resulted in a significant reduction in peak METS by 1.5 units, maximum speed by 0.5 km/hour, exercise time by 68.4 seconds with a significantly lower peak heart rate by 4.4 bpm, and lower percentage of age-predicted maximum heart rate by 2.5% (p<0.001 for all parameters). During each corresponding stage of the Bruce protocol, the average modified Borg score was found to be significantly higher in subjects exercising with mask after adjusting for age, gender and body mass index (p<0.03). Conclusion In a cohort of healthy individuals, wearing of a surgical face mask during maximal treadmill exercise lead to reduced physical performance and increased rate of perceived exertion. Individuals exercising with surgical masks need to be mindful of these limitations while undergoing physical training in order to differentiate these physiological responses from symptoms of early respiratory illness.